Note: Place factors alphabetically in the grid!
ab 2a 3b 6

**Weegy:** (a+3)(b+2)

**User:** Factor x 2 + xy - 2x - 2y.

**Weegy:** x(x+2)-y(x+2)= (x-y)(x+2)

**User:** Factor x^2 + xy - 2x - 2y.

**Weegy:** x(x+2)-y(x+2)= (x-y)(x+2)

**User:** Factor jm + jn + km + kn.

(More)8

x^2 + xy - 2x - 2y

= x(x + y) - 2(x + y)

= (x - 2)(x + y)

Added 2/26/2014 8:41:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by

jeifunk [2/27/2014 12:36:14 AM]

8

jm + jn + km + kn

= j(m + n) + k(m + n)

= (j + k)(m + n)

Added 2/26/2014 8:42:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by

jeifunk [2/27/2014 12:36:14 AM]